HUBUNGAN BUDAYA ORGANISASI, MOTIVASI KERJA DAN IMBALAN DENGAN KOMITMEN ORGANISASI KEPALA SMP NEGERI KOTA MEDAN - Edi Makmur Purba; Efendi Napitupulu; Sahala Siallagan (JURNAL PROINTEGRITA, 2021)
Lack of teacher commitment is indicated by the results of monitoring and evaluation (monev) of the Section Head and the Education Sector Team of the Medan City Education Office, which show that there are still many teachers who do not meet 6.25 hours per day of work. This study aims at finding the relationship between organizational culture, work motivation and rewards partially and simultaneously with the organizational commitment of the Head of the Medan City Junior High School. The population of this research is 45 people. A census sample is used to determine the number of samples and total amount of sample is 45 people. Data collection techniques in this study are questionnaires, interviews and documentation studies while the data analysis technique used is the classical assumption test, correlation analysis, partial test, simultaneous test and the coefficient of determination. The results show that the organizational culture variable had a positive and significant relationship with the organizational commitment of the Head of the Medan City Junior High School. The better the school organizational culture, the better the organizational commitment of the school principal. The work motivation variable has a positive and significant relationship with the organizational commitment of the Head of the Medan City Junior High School. The better the work motivation, the better the school principal's organizational commitment will be. Employee benefits variable has a positive and significant relationship with the organizational commitment of the Head of the Medan City Junior High School. The better the employee benefits, the better the school principal's organizational commitment will be. The variables of organizational culture, work motivation, and employee benefits simultaneously have a significant relationship with the organizational commitment of the Head of Medan City Junior High School, with an Fcount of 89.900> F table of 3.156, so a decision is made, H0 is rejected and Ha is accepted. As much as 85.20% of the variation in organizational commitment can be explained by organizational culture, work motivation, and rewards, while the remaining 14.80% is explained by other factors, such as variables of work facilities and leadership. It is recommended that school principals need to carry out their responsibilities with full awareness without any compulsion, while the government through the education office needs to provide broad opportunities for school principals to make policies related to schools. Principals need to be given opportunities to develop abilities through education and training, and principals who excel need to be given more appropriate rewards. The principal needs to be given an income by considering the overall work as a school principal, so that the overall income received is more satisfying for the principal. Further research is needed by other researchers using more independent variables to see the relationship with the principal's commitment.